2.\(3^{x+1}\)+\(3^{x+2}\)=135
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Mk giải câu 1 nha
1) 2x - 3 = x + 1/2
➡️2x - x = 1/2 + 3
➡️x = 7/2
Hok tốt~
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1:
\(A=\frac{1}{\left(1+2\right)}+\frac{1}{\left(1+2+3\right)}+\frac{1}{\left(1+2+3+4\right)}\)\(+\frac{1}{\left(1+2+3+4+5\right)}+...+\)\(\frac{1}{\left(1+2+3+...+10\right)}\)
\(A=\frac{1}{3}+\frac{1}{6}+....+\frac{1}{55}\)
\(A=2\left(\frac{1}{6}+\frac{1}{12}+....+\frac{1}{110}\right)\)
\(A=2\left(\frac{1}{2.3}+\frac{1}{3.4}+...+\frac{1}{10.11}\right)\)
\(A=2\left(\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+....+\frac{1}{10}-\frac{1}{11}\right)\)
\(A=2.\left(\frac{1}{2}-\frac{1}{11}\right)\)
\(A=\frac{9}{11}\)
Bài 2 :
2) Tử số = 11 x 13 x 15 + 3 x 3 x 3 x 11 x 13 x 15 + 5 x 5 x 5 x 11 x 13 x 15 + 9 x 9 x 9 x 11 x 13 x 15
= (1 + 3 x 3 x 3 + 5 x 5 x 5 + 9 x 9 x9) x 11 x 13 x 15 = (1+27+125+ 729) x 11 x 13 x 15
Mẫu số = 11 x 13 x 17 + 3 x 3 x 3 x 13 x 15 x 19 + 5 x 5 x 5 x 13 x 15 x 17 + 9 x 9 x 9 x 13 x 15 x 17 lớn hơn 11 x 13 x 15 + 3 x 3 x 3 x 13 x 15 x 17 + 5 x 5 x 5 x 13 x 15 x 17 + 9 x 9 x 9 x 13 x 15 x 17
= (1 + 3 x 3 x 3 + 5 x 5 x 5 + 9 x 9 x9) 13 x 15 x 17 = (1+27+125+729) x 13 x 15 x 17
\(\Rightarrow A< \frac{\left(1+27+125+729\right)\times11\times13\times15}{\left(1+27+125+729\right)\times13\times15\times17}\)
\(=\frac{11}{17}\)
\(=\frac{1111}{1717}=B\)
Vậy \(A=B\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1)\(A=\frac{1}{3}+\frac{1}{6}+...+\frac{1}{55}=2\left(\frac{1}{6}+\frac{1}{12}+...+\frac{1}{110}\right)=2\left(\frac{1}{2.3}+\frac{1}{3.4}+...+\frac{1}{10.11}\right)=2\left(\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+...+\frac{1}{10}-\frac{1}{11}\right)=2.\left(\frac{1}{2}-\frac{1}{11}\right)=\frac{9}{11}\)
2) Tử số = 11 x 13 x 15 + 3 x 3 x 3 x 11 x 13 x 15 + 5 x 5 x 5 x 11 x 13 x 15 + 9 x 9 x 9 x 11 x 13 x 15
= (1 + 3 x 3 x 3 + 5 x 5 x 5 + 9 x 9 x9) x 11 x 13 x 15 = (1+27+125+ 729) x 11 x 13 x 15
Mẫu số = 11 x 13 x 17 + 3 x 3 x 3 x 13 x 15 x 19 + 5 x 5 x 5 x 13 x 15 x 17 + 9 x 9 x 9 x 13 x 15 x 17
lớn hơn 11 x 13 x 15 + 3 x 3 x 3 x 13 x 15 x 17 + 5 x 5 x 5 x 13 x 15 x 17 + 9 x 9 x 9 x 13 x 15 x 17
= (1 + 3 x 3 x 3 + 5 x 5 x 5 + 9 x 9 x9) 13 x 15 x 17 = (1+27+125+729) x 13 x 15 x 17
=> \(A<\frac{\left(1+27+125+729\right)\times11\times13\times15}{\left(1+27+125+729\right)\times13\times15\times17}=\frac{11}{17}=\frac{1111}{1717}=B\)
Vậy A < B
![](https://rs.olm.vn/images/avt/0.png?1311)
a: 2x(x+1)-135=-200
=>2(x^2+x)=-65
=>2x^2+2x+65=0
=>x^2+x+32,5=0
=>x^2+x+0,25+32,25=0
=>(x+0,5)^2+32,25=0(vô lý)
b: 4x-5(x-1)+15=13
=>4x-5x+5=-2
=>5-x=-2
=>x=5+2=7
c: 2/3x-1/4=3/5-7/8
=>2/3x=3/5-7/8+1/4=24/40-35/40+10/40=-1/40
=>x=-1/40:2/3=-1/40*3/2=-3/80
d: 1/2(2x-3)+105/2=-137/2
=>1/2(2x-3)=-137/2-105/2=-242/2=-121
=>2x-3=-242
=>2x=-239
=>x=-239/2
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Câu 2:
a: \(=\left(-2\right)^3\cdot\left(-3\right)^3\cdot5^3=30^3\)
b: \(=3^3\cdot\left(-2\right)^3\cdot\left(-7\right)\cdot\left(-7\right)^2\)
\(=\left(3\cdot2\cdot7\right)^3=42^3\)
![](https://rs.olm.vn/images/avt/0.png?1311)
c) 135 - | 9 - x | = 3
| 9 - x | = 135 - 3
| 9 - x | = 132
=> 9 - x = 132
x = 9 - 132
x = 123
hoặc 9 - x = - 132
x = 9 - ( - 132 )
x = 9 + 132
x = 141
Vậy ..................
c) 135 - | 9 - x | = 35
\(2\left(x-1\right)+3\left(x-2\right)=x-4\)
\(2x-2+3x-6=x-4\)
\(5x-8=x-4\)
\(5x-8-x+4=0\)
\(4x-4=0\)
\(4x=4\)
\(x=1\)
\(3\left(4-x\right)-2\left(x-1\right)=x+20\)
\(12-x-2x+2=x+20\)
\(14-3x=x+20\)
\(14-3x-x-20=0\)
\(-6-4x=0\)
\(4x=-6\)
\(x=-\frac{3}{2}\)
\(\left|2x+3\right|=5\)
\(\Rightarrow\orbr{\begin{cases}2x=2\\2x=-8\end{cases}\Rightarrow\orbr{\begin{cases}x=1\\x=-4\end{cases}}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1/ Tính hợp lí:
\(\text{a/ ( - 16 ). ( - 25 ). ( - 12)}\)
\(=400.\left(-12\right)\)
\(=-4800\)
\(2\times3^{x+1}+3^{x+2}=135\)
\(3^{x+1}\left(2+3\right)=135\)
\(3^{x+1}\times5=135\)
\(3^{x+1}=\frac{135}{5}\)
\(3^{x+1}=27\)
\(3^{x+1}=3^3\)
x + 1 = 3
x = 3 - 1
x = 2